ACQUIRING ENGLISH SKILLS ABILITY THROUGH VIRTUAL SPEECH COMMUNITY - Ambar Pujiyatno (University of Muhammadiyah Purwokerto, 2017)
The aim in making Virtual speech community is to create a natural and enjoyable learning. It is a native speaker-like speech community that makes the learners live as if in the native speaking country.Some requirements are needed; they are members of the community, commitment, and rules. The members can be teachers, tutors, and learners. They must have commitment. Rules must cover everything that makes all activities run well. Members’ job descriptions are as follows: teachers teach the learners, tutors help the teachers teach the learner. Learners are the subject of learning who can acquire learning materials.The process of learning happens at every communication activities. The scopes of learning can be speaking, listening, writing, reading, grammar, vocabulary, and pronunciation. The learners can also learn how to communicate well and respect others. The result shows that they can improve their English and they have natural and enjoyable learning.